THE EFFECT OF USING GENIUS LEARNING STRATEGY ON STUDENTS’ ABILITY IN WRITING DESCRIPTIVE TEXTS - Dwi Sulistiani; Ashari P. Swondo (Universitas Potensi Utama, 2021)
The objectives of this research find out whether there is a significant effect of using genius learning strategy on student’s ability in writing descriptive texts. This research belongs to descriptive quantitative design to the eighth grade students of SMP Swasta Pelita Medan. The data was obtained using pre-test and post-test. Pre-test was given to both groups before treatment and post-test was given after treatment. The writer uses Genius Learning strategy as method to support students produce a descriptive text. The result of the study are; the value of the tobs was 9.741 the degree of freedom (df) is 28 at the level significance 0.05 is 1.701. It means the value of tobs is higher than ttable, the Alternative Hypotheses (Ha) is accepted and the Null hypotheses (Ho) is rejected. The researcher concluded that The Genius learning strategy significantly affects the ability of writing descriptive text to the eighth grade at SMP Swasta Pelita Medan.The writer suggests for the students of English Education Department should use the genius learning strategy as it has already been proven effective to improve student’s ability on writing.